Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if tan 2 a = 1 – e 2 then show that sec a + tan 3 a cosec a = (2-e 2 ) 3/2

if tan 2 a = 1 – e 2 then show that  sec a + tan 3 a cosec a = (2-e 2)3/2

Grade:12

2 Answers

Kaustubh Nayyar
27 Points
7 years ago
tan2a=1- e2      i.e.       sec2a =2-e2
seca + tan3a coseca = 1/cosa + sin2a/cos3a = 1/cosa + (1-cos2a)/cos3a
= 1/cosa + 1/cos3a – 1/cosa = 1/cos3a = sec3a = (2-e2)3/2
 
Rishi Sharma
askIITians Faculty 646 Points
one year ago
Dear Student,
Please find below the solution to your problem.

tan²θ=1-a²
LHS
=secθ+tan³θcosecθ
=√(1+tan²θ)+tan²θ×tanθ×√(1+cot²θ)
[∵, sec²θ-tan²θ=1 and cosec²θ-cot²θ=1]
=√1+(1-a²)+(1-a²)×√(1-a²)×√{1+(1/tan²θ)}
=√(2-a²)+(1-a²)×√(1-a²)×√{1+1/(1-a²)}
=√(2-a²)+(1-a²)×√(1-a²)×√{(1-a²+1)/(1-a²)}
=√(2-a²)+(1-a²)×√(2-a²)
=√(2-a²)×(1+1-a²)
=√(2-a²)×(2-a²)
=(2-a²)¹/²⁺¹
=(2-a²)³/²
=RHS (Proved)

Thanks and Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free